2018
DOI: 10.3762/bjoc.14.272
|View full text |Cite
|
Sign up to set email alerts
|

MoO3 on zeolites MCM-22, MCM-56 and 2D-MFI as catalysts for 1-octene metathesis

Abstract: Highly active olefin metathesis catalysts were prepared by thermal spreading MoO3 and/or MoO2(acac)2 on MWW zeolites (MCM-22, delaminated MCM-56) and on two-dimensional MFI (all in NH4 + form). The catalysts‘ activities were tested in the metathesis of neat 1-octene (as an example of a longer chain olefin) at 40 °C. Catalysts with 6 wt % or 5 wt % of Mo were used. The acidic character of the supports had an important effect on both the catalyst activity and selectivity. The catalyst activity increases in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Thus, based on their structural and textural characteristics, synthesized materials were qualified as a representative set of MWW zeolites with different acidities and architecture of crystalline layers 28,43 to be used for further study.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, based on their structural and textural characteristics, synthesized materials were qualified as a representative set of MWW zeolites with different acidities and architecture of crystalline layers 28,43 to be used for further study.…”
Section: Resultsmentioning
confidence: 99%
“…With the discovery of new advanced supports, such as zeolites and mesoporous molecular sieves, molybdenum and tungsten oxides particularly attracted the attention of many research groups in their efforts to increase the effectiveness of commercially important catalysts [9,63]. Several studies showed that various mesoporous siliceous materials (MCM-41 [15,64,65], KIT-6 [66]), or MWW-zeolites [65,67], and MFI-zeolites [65,67,68] were substantially more active than ordinary silica or silica-alumina. However, the most commonly used support was SBA-15 for its large pores and high BET areas.…”
Section: Heterogeneous Olefin Metathesis Catalysts Consisting Of Mo Amentioning
confidence: 99%
“…The beneficial effect of Al modification of the SBA-15 (Table 2, entry 8) was ascribed to the formation of Brønsted acid sites, which improve Mo dispersion. Conversely, acidity induces double bond isomerization and alkene oligomerization [67]. (ii) The dependence of activity on metal loading has a maximum: at high metal concentrations, the dispersion is imperfect, and a part of the metal forms metal oxide microcrystals, which do not contribute to the catalytic activity.…”
Section: Heterogeneous Olefin Metathesis Catalysts Consisting Of Mo Amentioning
confidence: 99%
“…800 K is required for dispergation of MoO3 over supports surface. Special attention was given to molybdate species resulted from MoO3 loading on aluminosilicate molecular sieves MCM-22, MCM-56 and 2D-MFI [23] and on siliceous molecular sieves MCM-41, MCM-48 and SBA-15 [24,25] which are active in olefins metathesis.…”
Section: Introductionmentioning
confidence: 99%